Integrating computational thinking to enhance students' mathematical understanding - Camilla Finsterbach Kaup; Pernille Ladegaard Pedersen; Torben Tvedebrink (Journal of Pedagogical Research, 2023)
This study aimed to examine whether a computational thinking (CT) intervention related to a) number knowledge and arithmetic b) algebra, and c) geometry impacts students' learning performance in primary schools. To this end, a quasi-experimental, nonequivalent group design was employed, with 61 students assigned to the experimental group and 47 students to the control group (n = 108). The experimental group comprised students in primary school who were to be followed across the second and third grades. The experimental group underwent work with digital CT activities, while the control group did not receive such interventions. A one-way analysis of variance (ANOVA) was performed on the data gathered to assess the ability differences between students from the experimental and control groups. The pre-and post-test results revealed that the experimental group's performance was significantly better than the control group's performance for the content areas involving CT activities.